Океан ненависти: [повести] / Чингиз Абдуллаев - Абдуллаев Чингиз Акифович (Вне закона, 1999)
Экземпляры: КХ (20191015) / Инвентарный номер: 46449 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 13 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6